The relationship between achievement goals and intrinsic motivation : state anxiety as a mediator - Manal Mohammad Asif (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2009)
In the present research the role of state anxiety as a mediator between achievement goals and intrinsic motivation for academic learning was examined. The direct relation between achievement goals as predictor variables and intrinsic motivation for academic learning as an outcome variable was investigated before conducting the mediational study. The achievement goals that were considered are mastery goal, performance-approach goal, performance-avoidance goal and Islamization goal. The participants were one hundred and forty one third and fourth year students, from International Islamic University Malaysia (IIUM). The Elliot's Achievement Goal Questionnaire (AGQ), the Intrinsic Motivation Inventory (IMI) and a self-tailored Islamization goal subscale were used for data collection. Hence, a post ex-facto correlational design was employed for the current study. It was hypothesized that performance-avoidance goal, relative to performance-approach and mastery goals will increase state anxiety which in turn will result in decreased intrinsic motivation for academic learning. It was also hypothesized that state anxiety would mediate the direct relation of Islamization goal and intrinsic motivation for academic learning. However, statistical analysis did not provide sufficient evidence to validate state anxiety as a mediator in the direct relations between all the achievement goals and intrinsic motivation for academic learning. Nevertheless, an important contribution of this study was the documentation of Islamization goal as a positive predictor of intrinsic motivation for academic learning.